Application of the approach of readiness levels for various subject areas in lean R&D - Sartori, A. V.; Gareev, A. R.; Ilyina, N. A.; Mantsevich, N. M. (Economics of Science, 2020)
The further development of the TPRL methodology as a tool for the commercialization of innovations is proposed. Descriptions of readiness metrics for lean R&D are presented. The expediency of subsequent decomposition of the readiness level criteria into the subject level and project levels for various technological / subject areas / complex systems is shown. Description of the initial scientific readiness levels SciRL are proposed for use in research dedicated to generating knowledge.